ANALYSIS OF COMPETITIVENESS OF THE TOURISM SECTOR EAST JAVA PROVINCE (A TECHNICAL EFFICIENCY & CONVERGENCE APPROACH) - Suparno, Suparno (Archives of Business Research, 2020)
This research analysis of tourism competitiveness is based on the very high disparity problem in the condition of the tourism sector in East Java Province. With a sample of 10 districts / cities and using investment data, tourist visits, population, government spending and tourism sector PDRB, it is produced that investment and tourist visits have a positive but not significant effect on tourism sector PDRB because due to the probability > 0.05. While the population and government expenditure have a positive and significant effect on the tourism sector PDRB due to the probability < 0.05. Fixed effect models that are formed are:PSP = 39485712 + 0.018 INV + 0.389 TOURIST + 22.304 POP + 0.065 GEX + e To measure tourism competitiveness, it is used with technical efficiency and total factor productivity where it is produced: Sidoarjo Regency, Malang City and Surabaya City are regencies / cities that have the highest level of technical efficiency with a value of 100% technical efficiency. Whereas with the calculation of total factor productivity in Gresik Regency (21,350), Jember Regency (16,543) and Kediri Regency (15,650) are regencies / cities that have the highest productivity. Based on the calculation of technical efficiency and total factor productivity results are obtainedL1) High efficiency and productive, Jember Regency; (2) High efficiency and less productive, Sidoarjo Regency, Malang City and Surabaya City; (3) Low and productive efficiency, Kediri Regency, Lamongan Regency and Gresik Regency; and (4) Low efficiency and less productive, Banyuwangi Regency, Pasuruan Regency and Pasuruan City. The spillover effect occurs in Pasuruan City, where the economy of Pasuruan City is affected by investments from Sidoarjo Regency and Surabaya City as indicated by the significance level of 0.051 Surabaya City investment and 0.048 for Sidoarjo Regency investment which means smaller and equal to 0.05. The calculation of convergence shows that the average convergence of regencies / cities in East Java to leader regions over 15 years and 5 months means that districts / cities need an average of 15 years and 5 months to match the conditions of tourism in the city of Surabaya.